Promoting competition and regulatory reforms in franchising electricity distribution - Dante B. Canlas; Karl Robert L. Jandoc (University of the Philippines, School of Economics (UPSE), 2025)
This study investigates how credit to firms responds to an energy price shock by comparing the credit growth of similar firms with different energy intensities before and after the shock triggered by the Russian invasion of Ukraine. Credit growth of energy-intensive firms declined by 8.75 percentage points. A large part of this decline stems from less risky firms drawing less on preexisting credit lines. Interest rate spreads for new loans rose for riskier firms. The results suggest that less risky firms reduced credit demand, whereas banks reduced supply of new loans to riskier firms.
Keywords: L94; L51; L41; 330; Electricity Distribution; Franchise Regulation; Competition Policy